1990
DOI: 10.3758/bf03197124
|View full text |Cite
|
Sign up to set email alerts
|

Implicit associative responses influence encoding in memory

Abstract: In list-learning experiments, the orienting question asked of one item may influence the processing of, and memory for, later items in the list. Four experiments demonstrated that words that are not related to their own orienting question, but that are semantically related to the question asked of a previous item, are better recalled than are words that are not related to any question in the list. Factors that influence this memory enhancement include the number of times relevant orienting questions appear dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This finding is consistent with recent studies reporting that variables that enhance memory also induce more false memory (McDermott & Roediger, 1998;Roediger & McDermott, 1995;Toglia, Neuschatz, & Goodwin, 1999). This pattern, the so-called "more is less" pattern (Toglia et al, 1999), reflects the activation of information available at encoding, and implies associative responses (Bryant, 1990;McDermott & Roediger, 1998;Roediger & McDermott, 1995;Underwood, 1965). From this perspective, the present results reflect the fact that the processing of related alternatives in the choice conditions induced more activation of nonpresented associates than did the processing of a single target item in the force conditions.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with recent studies reporting that variables that enhance memory also induce more false memory (McDermott & Roediger, 1998;Roediger & McDermott, 1995;Toglia, Neuschatz, & Goodwin, 1999). This pattern, the so-called "more is less" pattern (Toglia et al, 1999), reflects the activation of information available at encoding, and implies associative responses (Bryant, 1990;McDermott & Roediger, 1998;Roediger & McDermott, 1995;Underwood, 1965). From this perspective, the present results reflect the fact that the processing of related alternatives in the choice conditions induced more activation of nonpresented associates than did the processing of a single target item in the force conditions.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, in the studies in which predicted levels of recognition failure for weakly related pairs were reported, study-to-Ieam instructions were used, and the subjects were free to search for, or devise, some relation between the nominally unrelated iterns (cf. Bryant, 1990). In the current study, the subjects' study task was to make category membership judgments.…”
Section: Methodsmentioning
confidence: 99%
“…The problem for eaeh of the models deseribed arises from their simple eonception of encoding. Although there is growing evidenee that associative processes at encoding influenee later retrieval (see, e.g., Bryant, 1990;Nelson, McEvoy, & Schreiber, 1990), these models assume a relatively passive encoding process, relying on retrieval processes to explain recognition failure. The results of the present experiments demonstrate the eritieal role of encoding in determining the relation between reeall and reeognition.…”
Section: Constraints On Models Of Memorymentioning
confidence: 99%
“…The second item asked participants to 'List five words you think of when you consider the word sustainability'. The 'list five words approach' is used to provoke implicit associative responses (Bryant, 1990) that may be represented as conceptualisations.…”
Section: Data Collectionmentioning
confidence: 99%